A proposal for library programs for senior citizens at the Quezon City Public Library Novaliches Branch - Rozul, Patricia Dianne M.; Faderon, Rosalie B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
Senior citizens have their special needs that must be addressed such as health and their overall well-being and financial needs. This study aimed to determine what library programs can best address the library and information needs of senior citizens of Novaliches, Quezon City.
The study used the survey method. A total of 40 participants were randomly selected and survey questionnaires were distributed to the senior citizens of Novaliches. Also, an interview with the librarians and staff of the Quezon City Public Library (QCPL) Novaliches Branch was conducted to determine the library administrators/staff's perception of the characteristics, library and information needs and preference of senior citizens in their community.
Analyzing the data gathered for this study showed that senior citizens are receptive with the idea of having library programs for them. Almost all of the respondents were in favor of going to the library and participating in the programs specifically designed for them such as computer class, talks and discussions, film showing, book review, language class, storytelling, gaming/clubs and bible reading. Another alternative program which is the library on wheels also gained favor particularly from those respondents who have difficulty of physically going to the library. Moreover, the librarians and staff of QCPL Novaliches branch are also open to and receptive of any suggestions and improvements that will enhance the performance of the library. For senior citizens, the librarians are highly recommending the conduct of computer tutorials that will teach basic computer knowledge such as the use of computers, surfing the internet, accessing information to keep them informed on current events and in-contact with people in other parts of the world.
Recommendations of the study include areas of interest of senior citizens and their preferences where library programs can focus on. The information needs and interest of senior citizens include health which is their primary concern followed by hobbies and culture, then information about insurance, current events, needs regarding livelihood, socialization and household.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Quezon City Public Library Novaliches Branch; Older people -- Philippines -- Quezon City; Libraries and older people